Progress towards the enhanced synthesis of FK228 and analogs; and the total synthesis of Largazole-Azumamide hybrid - Troutman, Ann E., author; Williams, Robert M., advisor; Wood, John, committee member; Thamm, Douglas, committee member (Colorado State University. Libraries, 2009)
Progress towards an improved synthesis of HDAC inhibitor FK228 and work towards the completion of FK228 and Largazole Azumamide hybrids are presented. Through investigation of previous syntheses of FK228, a synthesis aimed at improving the overall yield and efficiency was planned out. After overcoming initial synthetic hurtles, a synthesis was attempted with moderate success. Further optimization would be needed for completion. Interest in creating Class specific HDAC inhibitors has gained popularity due to results of recent studies. The potent biological activity of FK228 and Largazole made them ideal candidates for modification. We were interested in developing these analogs by attaching side chains of other known HDAC inhibitors onto each macrocyle core, and in doing so we hoped to increase the reactivity of each molecule. Synthesis of the FK228-Azumamide hybrid began well, but hit several synthetic obstacles that have yet to be overcome. In contrast, the synthesis of Largazole- Azumamide hybrid proceeded smoothly, and was completed in thirteen steps and 11% yield. We are currently waiting for results of the biological activity studies.
Keywords: Histone deacetylase -- Synthesis -- Inhibitors; Amides -- Synthesis